Synthesis of Triamino Acid Building Blocks with Different Lipophilicities - Maity, Jyotirmoy; Honcharenko, Dmytro; Strömberg, Roger (PLOS ONE, 2015)
To obtain different amino acids with varying lipophilicity and that can carry up to three positive charges we have developed a number of new triamino acid building blocks. One set of building blocks was achieved by aminoethyl extension, via reductive amination, of the side chain of ortnithine, diaminopropanoic and diaminobutanoic acid. A second set of triamino acids with the aminoethyl extension having hydrocarbon side chains was synthesized from diaminobutanoic acid. The aldehydes needed for the extension by reductive amination were synthesized from the corresponding Fmoc-L-2-amino fatty acids in two steps. Reductive amination of these compounds with Boc-L-Dab-OH gave the C4-C8 alkyl-branched triamino acids. All triamino acids were subsequently Boc-protected at the formed secondary amine to make the monomers appropriate for the N-terminus position when performing Fmoc-based solid-phase peptide synthesis.